Scalp Rotation Flap for Reconstruction of Complex Soft Tissue Defects - Costa, Dary J.; Walen, Scott; Varvares, Mark; Walker, Ronald (Journal of Neurological Surgery Part B: Skull Base, 2016)
Importance Scalp reconstructions may be required after tumor resection or trauma. The inherent anatomy of the scalp presents challenges and may limit reconstructive options.Objective To describe and investigate the scalp rotation flap as a reconstructive technique for complex soft tissue defects.Design Retrospective case series with a mean follow-up of 13 months.Setting Tertiary academic center.Participants A total of 22 patients with large scalp soft tissue defects undergoing scalp rotation flap reconstruction.Interventions The flap is designed adjacent to the defect and elevated in the subgaleal plane. The flap is rotated into the defect, and a split-thickness skin graft is placed over the donor site periosteum.Main Outcomes and Measure Data points collected included defect size, operative time, hospital stay, and patient satisfaction with cosmetic outcome.Results Mean patient age was 71 years. Mean American Society of Anesthesiologist classification was 2.8. Mean defect size was 41 cm2 (range: 7.8–120 cm2), and 19 of 22 defects resulted from a neoplasm resection. Mean operative time was 181 minutes, and mean hospital stay was 2.4 days. There were no intraoperative complications. Three patients with previous radiation therapy had distal flap necrosis. Twenty-one patients (95%) reported an acceptable cosmetic result.Conclusions and Relevance The scalp rotation flap is an efficient and reliable option for reconstructing complex soft tissue defects. This can be particularly important in patients with significant medical comorbidities who cannot tolerate a lengthy operative procedure.
Keywords: oncology; scalp reconstruction; reconstruction; local flap